Terahertz Spectral Signatures of Ultrafast Spin Transports in Ferromagnetic Heusler Alloy (Adv. Phys. Res. 2/2023). Issue 2 (10th February 2023) - Jin, Zuanming; Guo, Yingyu; Peng, Yan; Zhang, Zeyu; Pang, Jinyi; Zhang, Zongzhi; Liu, Fan; Ye, Bin; Jiang, Yexin; Ma, Guohong; Zhang, Chao; Balakin, Alexey V.; et al.
Abstract : Ultrafast Spintronic Terahertz Emission In article number 2200049, Zuanming Jin and co‐workers show that the signature of ultrashort laser driven spin‐dependent transport in Co2 FeSi interfaced with a Pt layer is imprinted on the terahertz (THz) emission. THz spin currents in Co2 FeSi/Pt can be engineered by chemical ordering, interface roughness, and magnetization. The contributions to the ultrafast spin currents from thermalization and optical excitation of majority spins in Heusler alloy can be distinguished. Heusler alloy heterostructures may find future applications in spin‐based THz broadband emitters and polarization modulators.